INSTAGRAM COMO ESTRATEGIA DE MARKETING PARA JÓVENES EMPRENDEDORES EN BABAHOYO - CEDEÑO ANGULO WELLINGTON DANIEL (2024)
Due to the enormous influence of social networks, it is important to analyze the effectiveness of Instagram as a marketing strategy. This research will not only provide entrepreneurs with practical tools and strategies, but will also contribute to the academic field of digital marketing and entrepreneurship. Gaps in young entrepreneurs' knowledge of marketing strategies can hinder their ability to acquire digital resources and technical skills. In a context where marketing through Instagram is paramount, those who do not have digital skills or adequate knowledge of marketing tactics could be left behind, which would affect their ability to effectively take advantage of this platform. It is for this reason that our general objective of our research is to evaluate the Effectiveness of Instagram when used as a Marketing Strategy by young entrepreneurs in the city of Babahoyo, where it will benefit from a mixed research design, because it combines qualitative and quantitative methods and also focus group techniques, which will allow us to obtain a clearer and more complete understanding of what was investigated, where we will also apply surveys and interviews to get to know its effectiveness on Instagram.